Cyclolepis genistoides aqueous extract as source of neuroprotective agents - Alza, Natalia Paola (2021)
Since oxidative stress (OS) is a main component in neurodegenerative diseases, targeting this causative agent constitutes an important approach in drug discovery. In previous studies, we have selected the aqueous extract of Cyclolepis genistoides from a set of medicinal plants based on its ability to diminish metal-induced OS cellular markers. The aim of this work was to characterize the mechanism by which C. genistoides extract protected cells against OS. For this purpose, human neuroblastoma cells (IMR-32) were exposed to C. genistoides extract under conditions favoring OS (ferric ammonium citrate -FAC- exposure). C. genistoides extract (20 μg/mL) diminished the generation of superoxide anion in the presence of FAC. Moreover, the extract increased catalase activity when cells were exposed to FAC. Additionally, C. genistoides extract triggered the nuclear translocation of Nrf2, a cytoprotective transcription factor involved in antioxidant enzyme expression. The determination of flavonoids in C. genistoides extract revealed 16.1 ± 0.1 mg quercetin equivalents/g. To identify the bioactive components, 9 fractions (A-I) were obtained after a bio-guided fractionation. The evaluation of the main fractions F, G and H (20 μg/mL) showed that fractions F and H exposure reduced reactive oxygen species (ROS) production induced by FAC; however, fraction G treatment increased ROS levels. Until now, a sesquiterpene lactone was identified in fraction F. Our findings suggest that C. genistoides extract exerts the protective effect via the activation of cellular antioxidant defenses. Further studies are necessary to identify which compounds are responsible for the neuroprotective effect through Nrf2 modulation